Gray Matter Volume Abnormality in Chronic Pain Patients With Depressive Symptoms: A Systemic Review and Meta-Analysis of Voxel-Based Morphometry Studies - Ma, Teng; Ji, Yuan-Yuan; Yan, Lin-Feng; Lin, Jia-Ji; Li, Ze-Yang; Wang, Wen; Li, Jin-Lian; Cui, Guang-Bin (Frontiers in Neuroscience, 2022)
Altered gray matter volume (GMV) of brain regions has been widely reported as neuroplasticity features for chronic pain patients with depressive symptom for decades, while there still lack a consistent and significant result for further research. This study aimed to make a systemic review and meta-analysis to explore the characteristic brain regions in voxel-based morphometry (VBM) studies of this comorbidity disease. 18 studies (20 datasets) and 1320 participants (520 patients and 800 healthy controls) were selected from 1726 results searched from PubMed, MEDLINE, Web of Science and Cochrane Library databases. Significant coordinate information (x, y, z) reported in standard space and effective size (t value or z score) were extracted and analyzed by anisotropic effect size-signed differential mapping (AES-SDM) 5.15 software. According to the main analysis results, left hippocampus (HIP.L) showed consistent increased GMV, while the medial part of the left superior frontal gyrus (SFG.L, BA 10) showed significantly decreased GMV in chronic pain with depressive symptom. Subgroup analysis showed a smaller GMV in the medial orbital part of the right superior frontal gyrus (SFG.R, BA 10) in neuropathic pain; increased GMV in the right parahippocampal gyrus (PHG.R, BA 35), left hippocampus (HIP.L, BA 20), and right middle frontal gyrus (MFG.R) in musculoskeletal pain patients. Besides, meta-regression showed a positive relationship between the decreased GMV in the medial part of (SFG.L, BA 10) and female percentage of patients. Those brain areas (HIP.L and SFG.L, BA 10) are very robust and reproducible, which could be significant in this comorbidity disease, and provide a valuable reference to the future research.